Contribution of Changes in Synoptic‐Scale Circulation Patterns to the Past Summer Precipitation Regime Shift in Eastern China. Issue 12 (13th June 2020) - Zhou, Baiquan; Zhai, Panmao; Chen, Yang
Abstract: During the past few decades, eastern China has experienced a summer precipitation regime shift characterized by a "southern flood‐northern drought" pattern. Among numerous studies explaining this phenomenon, few have quantified dynamic‐thermodynamic contributions at daily‐synoptic scales. Using a self‐organizing map approach, summertime daily atmospheric flows during 1961–2015 are clustered into 20 circulation patterns (CPs), each of which is assigned to an attribute among wet, dry, and neutral according to their synchronous precipitation anomalies. We find that decreases in wet CPs for the north and increases (decreases) in wet (dry) CPs for the south are robustly significant and can well explain the contrasting precipitation trends. Dynamic and thermodynamic processes jointly produce more precipitation in the south but less precipitation in the northern half of the north region, with thermodynamic contributions being 30–40% larger. Dynamic influence and its interaction with thermodynamic factors dictate the latitudinal boundary between the drying and wetting regions. Plain Language Summary: Summer precipitation in eastern China has exhibited a "southern flood‐northern drought (SFND)" pattern during the past few decades. Despite substantial literature attempting to explain the phenomenon, efforts devoted to the quantification of contributions from dynamic processes (changes in daily atmospheric circulations) and thermodynamic processes (other physical processes such as the warming‐induced increasing water vapor in the air) appear to be deficient. Using a cluster method called self‐organizing map (SOM), the daily circulations in the summers during 1961–2015 are classified into 20 circulation patterns (CPs). The 20 CPs are further assigned to a wet, dry, or neutral attribute according to their synchronous precipitation anomalies. We demonstrate that the significant declining wet CPs for the north and significant increasing wet but decreasing dry CPs for the south can well explain the negative and positive precipitation trends in the north and south, respectively. Dynamic and thermodynamic processes both produce more precipitation in the south and less precipitation in the northern half of the north region, with thermodynamic contributions being 30–40% larger. Dynamic processes and its acting on thermodynamic processes play a particularly vital role in determining the latitudinal boundary between the positive and negative precipitation trends in eastern China. Key Points: Changing relative prevalence of wet and dry circulation patterns can well explain the summer precipitation regime shift in eastern China Dynamic and thermodynamic processes jointly shape the north–south contrasting pattern for precipitation trends Dynamic factors along with the dynamic‐thermodynamic interaction determine the latitudinal boundary between opposite precipitation trends